Massively Multiuser Virtual Environments using Object Based Sharing - Sonnenfroh, Michael; Möller, Kim-Thomas; Müller, Marc-Florian; Schoettner, Michael; Schulthess, Peter (Electronic Communications of the EASST, 2009)
Massively multiuser virtual environments (MMVEs) are becoming increasinglypopular with millions of users. Commercial implementations typicallyrely on a traditional client/server architecture controlling the virtual world state ofshared data at a central point. Message passing mechanisms are used to communicatestate changes to the clients. For scalability reasons our approach creates anddeploys MMVEs in a peer-to-peer (P2P) fashion. We use standard Java technologyimplementing only a few basic data-centric operations for the management of ourdistributed objects. Higher consistency models can easily be implemented usingthese basic operations. Currently, we have implemented transactional consistencyoffering convenient and consistent access to the shared scene graph. In this paperwe describe our basic object model and the prototype implementation TGOS (TypedGrid Object Sharing). Furthermore, we discuss preliminary measurements with thevirtual world Wissenheim executed on top of TGOS.